Case series of omalizumab for allergic bronchopulmonary aspergillosis in cystic fibrosis patients. Issue 2 (7th October 2016) - Nové‐Josserand, Raphaële; Grard, Soazic; Auzou, Lila; Reix, Philippe; Murris‐Espin, Marlène; Brémont, François; Mammar, Benyebka; Mely, Laurent; Hubert, Dominique; Durieu, Isabelle; Burgel, Pierre‐Régis
Summary: Allergic bronchopulmonary aspergillosis (ABPA) affects up to 15% of patients with cystic fibrosis (CF). Corticosteroids are used as first‐line therapy, but relapse and adverse effects commonly occur. Case reports have suggested the efficacy of the anti‐IgE recombinant humanized monoclonal antibody omalizumab. A retrospective multicenter observational French study retrieved 32 CF patients (11 children and 21 adults) who have received omalizumab for more than 3 months in the context of ABPA. Clinical characteristics, concomitant medications (inhaled and oral corticosteroids, antifungal drugs), lung function, body mass index (BMI), and serum IgE were compared at the start and during the first year of omalizumab therapy. Omalizumab‐related adverse effects and costs were also evaluated. No significant difference with omalizumab could be demonstrated with regard to lung function, BMI, or the number of patients receiving oral corticosteroids. At the time of initiation of omalizumab, 56% of patients were receiving oral corticosteroids. Five patients were able to discontinue corticosteroids during follow‐up and nine patients were able to reduce their daily dose. A total of 78% of the patients had received antifungal therapy at the time of the initiation of omalizumab. Treatment tolerance was good (12.5% of patients experienced side effects). The median cost of omalizumab treatment was €3, 620 per patient per month. Omalizumab may represent a steroid‐sparing therapy in CF patients with ABPA. A randomized‐controlled trial is urgently required to provide higher level of evidence regarding the efficacy and cost‐effectiveness of omalizumab in CF patients with ABPA.Pediatr Pulmonol. 2017;52:190–197. © 2016 Wiley Periodicals, Inc.